2003
DOI: 10.1002/ana.10491
|View full text |Cite
|
Sign up to set email alerts
|

A new mutation of the fukutin gene in a non‐Japanese patient

Abstract: Fukuyama-type congenital muscular dystrophy (FCMD), Walker-Warburg syndrome, and muscle-eye-brain disease are clinically similar autosomal recessive disorders characterized by congenital muscular dystrophy, cobblestone lissencephaly, and eye anomalies. FCMD is frequent in Japan, but no FCMD patient with confirmed fukutin gene mutations has been identified in a non-Japanese population. Here, we describe a Turkish CMD patient with severe brain and eye anomalies. Sequence analysis of the patient's DNA identified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
61
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
8
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 98 publications
(65 citation statements)
references
References 18 publications
4
61
0
Order By: Relevance
“…However, a recent report has identified several Japanese patients presenting with mild limb-girdle dystrophy (LGMD2M, MIM 611588) and normal intelligence (6) and who have a retrotransposal mutation and a point mutation in the fukutin gene. Outside Japan, fukutin mutations have been reported in patients with various phenotypes, from Walker-Warburg syndrome (WWS, MIM 236670) to LGMD (7)(8)(9)(10)(11)(12)(13). Overall, the current common understanding is that fukutin alterations can give rise to a wide spectrum of phenotypes.…”
mentioning
confidence: 99%
“…However, a recent report has identified several Japanese patients presenting with mild limb-girdle dystrophy (LGMD2M, MIM 611588) and normal intelligence (6) and who have a retrotransposal mutation and a point mutation in the fukutin gene. Outside Japan, fukutin mutations have been reported in patients with various phenotypes, from Walker-Warburg syndrome (WWS, MIM 236670) to LGMD (7)(8)(9)(10)(11)(12)(13). Overall, the current common understanding is that fukutin alterations can give rise to a wide spectrum of phenotypes.…”
mentioning
confidence: 99%
“…Both parents and the brother were heterozygous for this mutation. This is the first case worldwide in which a FKTN mutation has been found outside the Japanese population (Silan et al, 2003 FKTN and FKRP mutations in particular were much more common than previously suggested and were mostly identified in non-consanguineous patients of European descent (6/27 cases). All Ashkenazi Jewish patients in their group shared an identical haplotype at the FKTN locus and the same homozygous mutation c.1167_1168insA in exon 9 suggesting a founder effect in this population.…”
Section: Worldwide Distribution Of Fukutin Mutationmentioning
confidence: 70%
“…All the patients carrying the compound heterozygous mutations in the previous study had elevated serum CK concentrations, although they showed no or minimal skeletal muscle phenotypes. 14 The hyper-CKemia can also be found in the patients carrying FKTN mutations affected with FCMD 18 or LGMD. 19,20 These observations are in good agreement with the association between the FKTN mutations and hyper-CKemia.…”
Section: Discussionmentioning
confidence: 99%